Telescoping Colonic Anastomosis in Dogs: Gross and Microscopic Configurations - Aly Saber; Mohamed H Shekidef; Hamdy A. Fatih (Archives of Clinical and Experimental Surgery, 2012)
Introduction: Colorectal anastomotic leakage remains one of the most feared post-operative complications. The telescoping technique has been used but never widely acclaimed. The aim was to study both the external and internal features as well as the microscopic configuration of the invaginating colocolic anastomosis. Materials and Methods: After the scheduled three-week post-operative period, animals were reopened for a second-look laparotomy to detect: an external appearance of the anastomosis, internal appearance of the anastomosis and histopathological study. Results: Good and fair ratings were seen for external and internal appearance of the anastomosis, while no poor ratings were detected in our experiments. Microscopic study revealed a good healing process of the anastomotic lines. Conclusion: Our data showed that the telescopic anastomosis is a secure, easy to be constructed, fast and cheap procedure for colonic anastomoses. [Arch Clin Exp Surg 2012; 1(3.000): 151-157]